Soil test based fertilizer recommendation under for cumin in torripsamments of Rajasthan (Indian Journal of Arid Horticulture, 2025)
Soil test crop response correlation studies were conducted with cumin (var. RZ-209) under integrated plant nutrition system (STCR-IPNS) in Torripsamments of Rajasthan during rabi, 2004-05. Fertilizer adjustment equations under IPNS were formulated for cumin following Ramamoorthy's inductive-cum targeted yield model. The nutrient requirement for producing one quintal of cumin was found to be 4.06, 2.71 and 4.88 kg of N, P,O, and K,O, respectively. The per cent nutrient utilization efficiencies from soil and fertilizer nutrients were found to be 21.81 and 27.43 for N, 49.17 and 23.11 for P,O, and 15.59 and 50.93 for K,O, respectively. Likewise the per cent nutrient utilization efficiency from farm yard manure (FYM) was 7.43 for N, 11.22 for P,O, and 27.71 for K,O, respectively. In STCR-IPNS technology, the fertilizer doses are tailored to the requirements of specific yield targets of cumin taking into account the contribution from soil, fertilizers and organics.
Keywords: Cumin; STCR-IPNS; fertilizer adjustment equations; Torripsamments